wMel limits zika and chikungunya virus infection in a Singapore Wolbachia-introgressed Ae. aegypti strain, wMel-Sg. - Cheong Huat Tan; PeiSze Jeslyn Wong; Meizhi Irene Li; HuiTing Yang; Lee Ching Ng; Scott Leslie O'Neill (Public Library of Science (PLoS), 2017)
BACKGROUND:Zika (ZIKV) and Chikungunya (CHIKV) viruses are emerging Aedes-borne viruses that are spreading outside their known geographic range and causing wide-scale epidemics. It has been reported that these viruses can be transmitted efficiently by Ae. aegypti. Recent studies have shown that Ae. aegypti when transinfected with certain Wolbachia strains shows a reduced replication and dissemination of dengue (DENV), Chikungunya (CHIKV), and Yellow Fever (YFV) viruses. The aim of this study was to determine whether the wMel strain of Wolbachia introgressed onto a Singapore Ae. aegypti genetic background was able to limit ZIKV and CHIKV infection in the mosquito. METHODOLOGY/PRINCIPAL FINDINGS:Five to seven-day old mosquitoes either infected or uninfected with wMel Wolbachia were orally infected with a Ugandan strain of ZIKV and several outbreak strains of CHIKV. The midgut and salivary glands of each mosquito were sampled at days 6, 9 and 13 days post infectious blood meal to determine midgut infection and salivary glands dissemination rates, respectively. In general, all wild type Ae. aegypti were found to have high ZIKV and CHIKV infections in their midguts and salivary glands, across all sampling days, compared to Wolbachia infected counterparts. Median viral titre for all viruses in Wolbachia infected mosquitoes were significantly lower across all time points when compared to wild type mosquitoes. Most significantly, all but two and one of the wMel infected mosquitoes had no detectable ZIKV and CHIKV, respectively, in their salivary glands at 14 days post-infectious blood meal. CONCLUSIONS:Our results showed that wMel limits both ZIKV and CHIKV infection when introgressed into a Singapore Ae. aegypti genetic background. These results also strongly suggest that female Aedes aegypti carrying Wolbachia will have a reduced capacity to transmit ZIKV and CHIKV.